Catching up : what LDCs can do, and how others can help - Collier, Paul (Commonwealth Secretariat LondonGB, 2011)
Suggests a menu of strategic policies around which LDC governments might rally. Focuses on new opportunities arising from recent changes in the world economy. Emphasises the need for effective change and highlights potential future problems associated with the management of natural resources and the threat of climate change.